Synthesis of dibenzylamino-1-methylcyclohexanol and dibenzylamino-1-trifluoromethylcyclohexanol isomers. Issue 1 (15th October 2015) - Jones, D. Heulyn; Bresciani, Stefano; Tellam, James P.; Wojno, Justyna; Cooper, Anthony W. J.; Kennedy, Alan R.; Tomkinson, Nicholas C. O.
Abstract : Saturated isomers of the 1, 2- 1, 3- and 1, 4-aminophenol pharmacophore have been prepared. Abstract : The isomers of dibenzylamino-1-methylcyclohexan-1-ol and dibenzylamino-1-trifluoromethylcyclohexan-1-ol have been prepared. The stereochemistry of these compounds was unequivocally assigned through a combination of NMR spectroscopy and single crystal X-ray analysis. The cis -isomer of 3- N, N -dibenzylamino-1-trifluoromethylcyclohexanol and its derivatives display an unusual conformational behaviour in both solution-phase and the solid-state, where the amino group usually adopts an axial conformation.